2018
DOI: 10.1111/php.12902
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy as a Co‐adjuvant in Endodontic Treatment of Deciduous Teeth: Case Series

Abstract: To assure the success of endodontic treatment, the root canal must be completely decontaminated. Thus, some methods have been researched in an attempt to effectively eliminate microorganisms from the interior of the root canal system. Among them is conventional endodontic therapy in conjunction with photodynamic therapy (PDT). Five anterior deciduous teeth were treated endodontically with the conventional technique and PDT. For PDT, 0.005% methylene blue was used as a photosensitizer and a 660 nm laser. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Microbiological samples of the infected and disinfected root canal were taken, and the bacterial colonies were examined under a microscope. The results showed a bacterial reduction from 37.6% to a whopping 100%, further underlying the statement that PDT can be considered an alternative method to act as a support to root canal disinfection [93]. Compared with irrigation by the conventional sodium hypochlorite (which is considered to be the gold standard for root canal irrigation), PDT has shown very promising results.…”
Section: Pdt In Endodonticsmentioning
confidence: 76%
See 1 more Smart Citation
“…Microbiological samples of the infected and disinfected root canal were taken, and the bacterial colonies were examined under a microscope. The results showed a bacterial reduction from 37.6% to a whopping 100%, further underlying the statement that PDT can be considered an alternative method to act as a support to root canal disinfection [93]. Compared with irrigation by the conventional sodium hypochlorite (which is considered to be the gold standard for root canal irrigation), PDT has shown very promising results.…”
Section: Pdt In Endodonticsmentioning
confidence: 76%
“…Recently, research has been conducted to support the use of PDT in conjunction with conventional chemo-mechanical preparations (Figure 4) [92]. The most recent evidence was shown by Okamoto et al; after conventional root canal treatment was carried out on five anterior and deciduous teeth, PDT was conducted using the photosensitizer methylene blue and a 660 nm laser light [93]. The root canal was then irrigated with saline and a sealant was placed.…”
Section: Pdt In Endodonticsmentioning
confidence: 99%
“…Therefore, it is important to use additional techniques that may offer assistance with antimicrobial activity [7,8]. Different studies have concluded that photodynamic therapy can aid in the endodontic treatment of deciduous teeth, resulting in a significant reduction in the number of microbiota present in deciduous teeth with necrotic pulp [1,9]. Photodynamic antimicrobial therapy (aPDT) is based on the concept that a non-toxic dye, known as photosensitizer (FS), can be activated by low doses of visible light and an appropriate wavelength to generate singlet oxygen and free radicals, which are cytotoxic to bacterial cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Blue dyes, especially toluidine blue and methylene blue, used with a low-intensity laser are effective in eliminating bacteria [11]. Photodynamic therapy has been used in some studies as a support for the elimination of microorganisms, along with the mechanical-chemical preparation of the root canals of deciduous teeth [1,6,8,9,12]. The aPDT can then be an auxiliary therapy to reduce the microbiota in the endodontic treatment of deciduous teeth [1,6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation